Diversity, Species Composition, and Relative Abundance of Avifauna at Debre Libanos Monastery, Ethiopia - Desalegn, Tamenut; Negussie, Fasika (International Journal of Zoology, 2022)
Data on avifaunal diversity and distribution are vital to enhance and inform conservation efforts. Therefore, this study was conducted to explore the diversity, distribution, and relative abundance of bird species in the Derbe Libanos Monastery Forest. The data were collected from December 2019 to September 2020, covering both the wet and dry seasons. Natural forest, plantation, cliff forest, and settlement were identified as an important habitat for the birds using a stratified random sampling design based on vegetation composition and characteristics. Point counts were employed to identify and record birds in the four habitat types. During the study, 61 avian species belonging to 13 orders and 31 families were identified. The highest diversity (H′ = 3.43) and evenness (E = 0.96) were observed in the summer season in natural forests. The difference in abundance of bird species was statistically significant between observed and expected counts of each species in different habitats (χ2 = 629.97, df = 60, and p<0.001). Recognizing that the monastery forest has a large number of bird species, enhanced avian monitoring and forest reintegration opportunities should be prioritized for conservation.